Construction of an educational booklet about the paediatric surgical process: experience using cordel literature (Research, Society and Development, 2021)
Objective: to relate the process of constructing a pediatric oriented cartilage in the form of a cordel and its importance for the protagonism of children and their families during surgical life. Method: This is an experience report, developed by students and teachers at a public university in Pernambuco, during the experience of remote teaching in the period from September to November 2020. The construction was carried out in four stages: bibliographic survey, preparation of the cordel, design of the booklet, and evaluation. Results: the activity resulted in the cordel-format booklet ''The day of my surgery'', which facilitates the understanding of children and their families about the surgical procedure, and provides guidance in a relaxed way. Final considerations: the cordel-format booklet was configured as an accessible, playful, creative, and didactic resource, which dialogues with the popular culture of the Northeast, and can potentiate popular education in health, as a health promotion strategy in the hospital context.